Rational Emotive Behavior Therapy: Is There Something New? Identifying Its Benefits in Education Counseling of the Literature from 2014–2024 - Abi Fa’izzarahman Prabawa; Nur Hidayah; Henny Indreswari; Adi Atmoko; Eni Rindi Antika (PD ABKIN JATIM Open Journal System, 2024)
This research explores the development and efficacy of Rational Emotive Behavior Therapy (REBT) in educational settings over the last decade, emphasizing its potential to improve students’ mental well-being and academic performance. A systematic review of 13 articles published between 2014 and 2024 reveals advancements in REBT, such as incorporating neurobiological perspectives and technology, adjustments for online learning, and tailored interventions for at-risk groups. The findings indicate that REBT effectively addresses various psychological challenges, including math anxiety, exam-related stress, and bullying, contributing to a nurturing learning environment. Additionally, the study highlights the importance of training REBT educators to manage their stress and enhance classroom dynamics. While the results show positive outcomes for both students and teachers, limitations include a small sample size and a narrow focus on specific populations. The study calls for further research to confirm REBT’s relevance in diverse educational settings, emphasizing its role in fostering resilience and mental well-being for students and educators alike. Keywords: Rational Emotive Behavior Therapy, REBT, School, Counseling